Our approach to sinonasal inverted papillomas - Çukurova, İbrahim (ENT Updates, 2012)
Objective: Our aim is to emphasize the efficacy of endoscopic endonasal approach in patients diagnosed as inverted papilloma with limited histopathologic data. Methods: Forty patients who had preoperative diagnosis of inverted papilloma in our clinics, and operated between October 2002 and May 2012 were retrospectively analyzed. These patients had undergone medial maxillectomies using endoscopic transnasal (n=38) or external lateral rhinotomy (n=2) approach. The purpose of preferring external approach for lateral rhinotomy was that one of the patients was diagnosed as epidermoid carcinoma, and the other patient had intense scar tissue due to the previous operation performed in another medical center with resultant distorted normal anatomic structure. Results: Mean age of 40 patients operated for the diagnosis of inverted papilloma was 54±9.43 (range 27 to 81) years. While the main complaint of the patients was nasal stuffiness, the other complaints were rhinorrhea, headache, postnasal drainage, olfactory problems, mass lesion protruding out from nasal cavities, sense of pressure, and pain on face, nosebleed, snoring, and dry mouth. Among 40 patients 55 different anatomic regions were affected, and in some patients the tumor was originated from 2 or 3 regions. Any problem was not encountered in 38 patients whom we operated using transnasal endoscopic method during an average postoperative follow-up period of 55.8 (range 2 to 112) months. Conclusion: Transnasal endoscopic surgery is an effective and safe method in selected cases with inverted papilloma.